Database-driven charting using XSLT and SVG controlling finer details of data-driven scalable vector graphics. - Moharil, Avinash (XML journal :the ultimate enterprise resource.)
Over the last few years, there have been significant developments in the XML world. Many enterprises have adopted XML for various purposes such as data transfer, reporting, client-tier presentation, server to server communication and so on.